Molecular cloning of AGPase large subunit I gene and construction of its sense, antisense and RNAi expression vectors - KANG Guo-zhang; ZHANG Meng-qin; GUAN Chun-yun; GUO Tian-cai; ZHU Yun-ji (浙江大学学报. 农业与生命科学版)
To study the function of AGPase large subunit I gene (LSU I) in synthesis of starch in wheat plants, full cDNA sequences (1947 bp) of a LSU I gene (GenBank No. DQ839506) were cloned from grains of common wheat (Triticum aestivum, Yujiao 2 cultivar) with RT-PCR, and its sense, antisense and RNAi vectors were also constructed. The coding regions of LSU I were 1569 bp (from 117-1685 bp), which shared high homogeneity with Z21969 gene sequences. The cloned LSU I gene had two different bases with the Z21969 (T/C, at 851 bp site; and G/A, at 926 bp site), but the two differences did not change their amino sequences, implying the function of the cloned LSU I was not affected. The sense and antisense expression vectors of LSU I were constructed, in which the coding region of the gene was placed under the 35S promoter in either sense or antisense orientation. In addition, especial 250 bp fragments of LSU I were also cloned, and this fragment was inserted into pFGC5941 vector to construct RNAi expression vector of LSU I. These constructed vectors provided a good background to study the function of LSU I.